Preliminary experience on safety of regorafenib after sorafenib failure in recurrent hepatocellular carcinoma after liver transplantation. Issue 11 (3rd September 2019) - Iavarone, Massimo; Invernizzi, Federica; Czauderna, Carolin; Sanduzzi‐Zamparelli, Marco; Bhoori, Sherrie; Amaddeo, Giuliana; Manini, Matteo A.; López, Miguel F.; Anders, Margarita; Pinter, Matthias; Rodríguez, Maria J. B.; Cristóbal, Mario R.; et al.
Abstract : Regorafenib is one option for second‐line treatment of hepatocellular carcinoma (HCC), improving overall survival (OS) of sorafenib‐tolerant patients who develop progression. We aim to evaluate the safety and outcomes of regorafenib as second‐line treatment for HCC recurrence after liver transplantation (LT). This is a retrospective, multicenter, international study including regorafenib‐treated LT patients (2015‐2018), with analysis of baseline characteristics and evolutionary events during sorafenib/regorafenib treatment. Twenty‐eight LT patients (57 years, 7% cirrhotics, 54% performance status 1) were included. Median time from LT to regorafenib initiation was 3.9 (1.1‐18.5) years; median time on sorafenib was 11.3 (0.7‐76.4) months and 14 (1‐591) days from sorafenib discontinuation to regorafenib. During regorafenib (6.3 months), all patients had at least one adverse event (AE), the most common grade 3/4 AEs were fatigue (n = 7) and dermatological reaction (n = 5). While no liver rejection was observed, plasma levels of immunosuppressive drugs increased in five. Twenty‐four patients developed progression (38% extrahepatic growth, 33% new extrahepatic lesions/vascular invasion). Median OS from regorafenib initiation was 12.9 (95% CI, 6.7‐19.1) and 38.4 months (95% CI, 18.5‐58.4) for the sorafenib initiation. This is the first study showing safety of regorafenib after LT, thus providing the rational of considering regorafenib in the clinical decision‐making in sorafenib‐tolerant patients with HCC recurrence after LT. Abstract : This multicenter, international observational cohort study shows the safety of regorafenib in patients with recurrence of hepatocellular carcinoma after liver transplantation who tolerated sorafenib even though developing progression.